By-products of the whelk processing industry as valuable source of bioactive peptides (Proceedings of the World Conference on Waste Management, 2021)
The fish and shellfish industry processes 851,984 tonnes of fish per year worldwide. However, only 43% of that is consumed, and valuable proteins that are going to waste. Protein hydrolysates are widely used in food technology for their nutritional and functional properties. The goal of this project is to extract protein from the shellfish processing industry by-products and create protein hydrolysates that have marketable value. The waste was divided into two types: raw waste (R) and cooked waste (C). The proteins were extracted using the pH shift method at acid (A), neutral (N) and basic (B) pH, they were then quantified using the Bradford assay, for which R had the highest protein yield. Proteins were also qualified using reverse phase high-performance liquid chromatography (RP-HPLC) that showed that R has more hydrophilic proteins while the C protein showed more peaks in the hydrophobic phase. The Fourier-transform infrared spectroscopy (FTIR) indicated the presence of glutamine, tyrosine and serine in the extracted proteins. Extracted proteins were then hydrolyzed using Alcalase and α-Chymotrypsin and the degree of hydrolysis measured with a 2,4,6-Trinitrobenzene Sulfonic Acid (TNBS) assay. It was possible to obtain higher degrees of hydrolysis (DH) of using Alcalase. The hydrolysates were tested for antioxidant activity using the DPPH (2,2-diphenyl-1-picryl-hydrazyl-hydrate) free radical antioxidant assay. Alcalase hydrolysates showed to have an IC50 for the DPPH assay of 33.79±2.96 µg/mL, 13.92±1.57 µg/mL and 36.09±3.04 µg/mL, and α-Chymotrypsin hydrolysates 43.24±2.11 µg/mL, 81.18±4.07 µg/mL and 56.02±2.29 µg/mL for A, N and B protein, respectively. The IC50 results obtained are significantly lower than the ones described in other studies using the same enzymes or other marine species. This can indicate that more heterogenous mixtures of by-product can originate extracted proteins that when hydrolyzed lead to higher radical scavenging activity.
Keywords: Shellfish; Bioactive peptides; Protein extraction; Protein hydrolysates; Waste management; Nutraceuticals; Antioxidants